2021
DOI: 10.1093/biolinnean/blaa204
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and biogeography of an ancient frog clade from the Guiana Shield (Anura: Microhylidae:Adelastes,Otophryne,Synapturanus) exhibiting spectacular phenotypic diversification

Abstract: The outstanding biodiversity of the Guiana Shield has raised many questions about its origins and evolution. Frogs of the genera Adelastes, Otophryne and Synapturanus form an ancient lineage distributed mostly across this region. These genera display strikingly disparate morphologies and life-history traits. Notably, Synapturanus is conspicuously adapted to fossoriality and is the only genus within this group to have dispersed further into Amazonia. Moreover, morphological differences among Synapturanus specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 83 publications
(127 reference statements)
2
28
0
1
Order By: Relevance
“…Besides imposing transient physical barriers to gene flow, volcanic eruptions may also favour divergence through local adaptation when populations become isolated in distinct environments. This hypothesis is consistent with associations of the two caecilian lineages within distinct precipitation regimes and habitats across the island (Figure 4), which may reflect local adaptation to specific soil microhabitats (Torres‐Sánchez et al, 2019) as demonstrated in other fossorial vertebrates (Fouquet et al, 2021; Martín et al, 2013). Associations between habitat type and lineage divergence were also reported in reed frogs (Bell & Irian, 2019) and fruit flies (Coyne et al, 2002; Matute & Coyne, 2010) on São Tomé, suggesting that this pattern may be widespread across a variety of organisms on the island, although the specific mechanisms of local adaptation are likely to differ between fossorial versus surface‐dwelling taxa.…”
Section: Discussionsupporting
confidence: 84%
“…Besides imposing transient physical barriers to gene flow, volcanic eruptions may also favour divergence through local adaptation when populations become isolated in distinct environments. This hypothesis is consistent with associations of the two caecilian lineages within distinct precipitation regimes and habitats across the island (Figure 4), which may reflect local adaptation to specific soil microhabitats (Torres‐Sánchez et al, 2019) as demonstrated in other fossorial vertebrates (Fouquet et al, 2021; Martín et al, 2013). Associations between habitat type and lineage divergence were also reported in reed frogs (Bell & Irian, 2019) and fruit flies (Coyne et al, 2002; Matute & Coyne, 2010) on São Tomé, suggesting that this pattern may be widespread across a variety of organisms on the island, although the specific mechanisms of local adaptation are likely to differ between fossorial versus surface‐dwelling taxa.…”
Section: Discussionsupporting
confidence: 84%
“…However, genetic, morphological and acoustic variation across this range suggests that some of these populations may not belong to S. mirandaribeiroi. The similarity between the skull and humerus of the paratype (MNHN-RA-1974.0397) and that of specimens from southwestern French Guiana, Suriname and the Manaus region, an area encompassing the type locality of S. mirandaribeiroi, strongly suggests conspecificity (Fouquet et al, 2021). Moreover, genetic data indicate that these specimens form a lineage related to populations located in the southern part of the Amazon River basin (Synapturanus sp.…”
Section: Introductionmentioning
confidence: 87%
“…Within the Neotropics, microhylids represent 18% of the total number of described species (Frost, 2021) and belong to two major groups: Gastrophryninae Fitzinger, 1843, the most species rich subfamily with 81 species (Frost, 2021) distributed from southern North America to Argentina; and a species poor clade formed by the monotypic Adelastinae Peloso, Frost, Richards, Rodrigues, Donnel dergo endotrophic development (Nelson & Lescure, 1975;Pyburn, 1975;1977;Menin et al, 2007). Although no direct observations have been reported, the overall morphology, and notably the shape of the snout and humerus, suggest a head-first, forward-burrowing, behavior (Keeffe & Blackburn, 2020;Fouquet et al, 2021). Overall, Synapturanus are poorly known, and the scarcity of basic data on their life-history and rarity in zoological collections is easily explained by their secretive lifestyle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…en el departamento de Vaupés, región Amazonía. Por el contrario, los últimos cantos de anuncio descritos al momento de finalizar nuestra revisión fueron para las especies Pristimantis alius, P. ingles y Synapturanus salseri [68,69]. El canto de anuncio ha sido descrito más de una vez para el 53.4% de las especies (n = 164 spp.…”
Section: Cantos De Anuncio Descritosunclassified